Application of Model Predictive Controller to Magnetic Levitation - Novotný, Aleš; Honc, Daniel (IEEE (Institute of Electrical and Electronics Engineers), 2023)
Model Predictive Control (MPC) is an advanced process control method that is widely used for controlling both linear and under some modifications for non-linear systems. The aim of this work is to show a way how to apply MPC to a non-linear Magnetic Levitation System (MLS) and its capability of stabilization and closed-loop performance. This work is a continuation of the previous article where the laboratory plant CE 152 MLS was identified, and a non-linear model was designed. This paper proposes a control circuit consisting of linearized discretized non-linear MLS model, Extended Kalman Filter (EKF) algorithm for state estimation and linear MPC. The results are verified in simulation and real-world experiment.
Aplikace prediktivního regulátoru na magnetickou levitaci
Keywords: extended Kalman filter; laboratory plant CE 152; magnetic levitation system; model predictive control; non-linear system; rozšířený Kalmanův filtr; laboratorní zařízení CE 152; magnetický levitační systém; prediktivní řízení; nelineární systém